IDENTIFIKASI CEKUNGAN HIDROKARBON “RAE” BERDASARKAN DATA MAGNETOTELURIK DI DAERAH BULA, MALUKU - Gita Purna Rae Wanudya; Syamsurijal Rasimeng; Rustadi Rustadi; Noor Muhammad Indragiri (Jurnal Geofisika Eksplorasi, 2018)
The research had been performed using Magnetotelluric to get a 2D model based on variations in resistivity of the subsurface rock. The purpose of this study was to determine the hydrocarbon formation zone. The research method to achieve the research objectives, among others, the first filtering performed on the data with a robust process. This process consists of Robust No Weight, Robust Rho Variance and Ordinary Cohenerency. The second step is done to change the format Selection XPR And Edi. A third inversion resistivity model for the review get a 2D cross section. Based on the findings of the eight data processing methods of measurement points obtained information Magnetotelluric rock formations. Formation hidrokrabon What are the areas is research a reservoir and caprock. The layer in 1600 m – 2700 m depth from the surface which resisvity 12 -33 m assumpted as clay cap. While the layer in 2700 m – 5000 m depth from the surface with high resistivity 41- 250 m is assumpted as oil sands (reservoir). The trap zone of this hidrocarbon formation categorized into structural trap which is the trap of anticline.